2010
DOI: 10.2174/1874350101003010009
|View full text |Cite
|
Sign up to set email alerts
|

Race and IQ: A Theory-Based Review of the Research in Richard Nisbett ’ s Intelligence and How to Get It

Abstract: We provide a detailed review of data from psychology, genetics, and neuroscience in a point-counterpoint format to enable readers to identify the merits and demerits of each side of the debate over whether the culture-only (0% genetic-100% environmental) or nature + nurture model (50% genetic-50% environmental) best explains mean ethnic group differences in intelligence test scores: Jewish (mean IQ = 113), East Asian (106), White (100), Hispanic (90), South Asian (87), African American (85), and sub-Saharan Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 169 publications
2
30
0
7
Order By: Relevance
“…Subsequently, Wicherts and Johnson (2009) criticized this study for using "unreliable" item-level analyses, even though the items found relatively difficult (or easy) by twins in North America were the ones found relatively difficult (or easy) by the Roma in Serbia, and by Whites, South Asians, Coloreds, and Blacks in South Africa (mean r = 0.87). However, Rushton and Jensen (2010) corroborated the results after organizing the items into more reliable parcels, each containing six or more items. As the heritability of the parcels increased, so did the mean group differences (mean r = 0.74; P b 0.01).…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Subsequently, Wicherts and Johnson (2009) criticized this study for using "unreliable" item-level analyses, even though the items found relatively difficult (or easy) by twins in North America were the ones found relatively difficult (or easy) by the Roma in Serbia, and by Whites, South Asians, Coloreds, and Blacks in South Africa (mean r = 0.87). However, Rushton and Jensen (2010) corroborated the results after organizing the items into more reliable parcels, each containing six or more items. As the heritability of the parcels increased, so did the mean group differences (mean r = 0.74; P b 0.01).…”
Section: Introductionsupporting
confidence: 59%
“…In a technical Appendix, "The Case for a Purely Environmental Basis for Black/White Differences in IQ," the author critiques our position (the default hypothesis of behavior genetics) that both individual and group differences are the result of both nature and nurture (Jensen, 1969(Jensen, , 1973(Jensen, , 1998Rushton, 1995, Rushton & Jensen, 2005, along with many conclusions from The Bell Curve (Herrnstein & Murray, 1994). We have replied to the arguments in Nisbett's book in detail (Rushton & Jensen, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that it may be open to criticisms (for a debate see Rushton and Jensen, 2010;Wicherts and Johnson, 2009) the method can offer further information useful in the present context. With our present data set, it was possible to run analyses at this level only for the case of the 310 North Italy and 313 South Italy 10 th -graders tested with the reading comprehension test (20 items).…”
Section: Mt-advanced Datamentioning
confidence: 97%
“…As such, boosting these traits in poor countries should be relatively easy. To date, results of intervention efforts have been mixed at best, and nowhere close to 19 cm in height or 20 IQ points [56], ([65] and its critique in [66]), [67,68]. The ability to intervene so as to speed up IQ gains, in genetically informed studies such as those using siblings as controls, should be considered the ultimate test of any environmental hypothesis for the Flynn effect.…”
Section: Suggestion 4: Conduct More and Better Intervention Programsmentioning
confidence: 99%